Prevalence and Risk Factors Associated with S. haematobium Egg Excretion during the Dry Season, Six Months following Mass Distribution of Praziquantel (PZQ) in 2017 in the Bafia Health Area, South West Region Cameroon: A Cross-Sectional Study - Vicky Daonyle Ndassi; Judith Kuoh Anchang-Kimbi; Irene Ule Ngole Sumbele; Godlove Bunda Wepnje; Helen Kuokuo Kimbi (Journal of Parasitology Research)
Background. A selective population mass drug administration of PZQ involving school-aged children was carried out in the Bafia Health Area in April 2017. This study investigated the prevalence, intensity, and factors associated with S. haematobium egg excretion in this foci during the dry season, six months after the chemotherapy campaign. Methods. A cross-sectional study including 1001 consenting individuals (aged 3-62 years) was carried out in three localities (Ikata, Bafia, and Munyenge) in the Bafia Health Area between November 2017 and January 2018. Information on sociodemographic, stream usage, and contact behaviour was documented. Schistosoma haematobium ova in urine were detected using membrane filtration technique. Results. The prevalence of S. haematobium egg excretion was 8% with a higher level recorded in Munyenge (13.2%) than Ikata (7.5%) and Bafia (2.8%). The difference was significant (p < 0.001). Equally, Munyenge had the highest infection intensity (36.36 range: 2-200) when compared with Ikata (16.25 range: 2-57) and Bafia (8.0 range: 0-8). Although the age group (5–15 years) was significantly (p < 0.001) associated with more exposure to infested water, this group was less likely (OR: 0.42 95% CI: 0.19-0.91) associated with S. haematobium egg excretion. The risk of egg excretion increased by 4.79 times (95% CI: 2.20-10.41) and 3.68 times (95% CI: 1.59-8.54) among residents in Munyenge and Ikata, respectively. Similarly, frequency to the stream (> thrice/day) was significantly higher (χ2 = 58.73; p < 0.001) in Munyenge. Frequent contact (three visits/day) with stream correlated with highest odds of egg excretion (OR: 8.43 95% CI: 3.71-19.13). Conclusion. The prevalence of S. haematobium egg excretion was low during the dry season. This was most likely attributed to the preventive campaign with PZQ and may parallel low transmission potentials in infested waters during this period.